2004
DOI: 10.1103/physrevlett.92.175504
|View full text |Cite
|
Sign up to set email alerts
|

Driving Force of Stacking-Fault Formation in SiCpinDiodes

Abstract: The driving force of stacking-fault expansion in SiC p-i-n diodes was investigated using optical emission microscopy and transmission electron microscopy. The stacking-fault expansion and properties of the partial dislocations were inconsistent with any stress as the driving force. A thermodynamic free energy difference between the perfect and a faulted structure is suggested as a plausible driving force in the tested diodes, indicating that hexagonal polytypes of silicon carbide are metastable at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 20 publications
5
45
3
Order By: Relevance
“…Silicon carbide (SiC) is a particularly important and interesting material since it has over 200 crystalline polytypic structures with common structural units of face-centred cubic zinc blende (ZB), hexagonal close-packed wurtzite (WZ) and rhombohedral structures [1]. Among these polytypes, the 4H-SiC structure with a bandgap of $3.2 eV possesses favourable electrical properties, including high electron mobility [3,4], making SiC an attractive candidate for "green energy" components in high-power electronic applications because of the potential for saving electric power and reducing CO 2 emission [5][6][7][8][9][10]. The mechanical behaviour of semiconductor materials is an important topic since the performance (such as functionality and reliability) of electronic devices strongly depends on their mechanical properties [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is a particularly important and interesting material since it has over 200 crystalline polytypic structures with common structural units of face-centred cubic zinc blende (ZB), hexagonal close-packed wurtzite (WZ) and rhombohedral structures [1]. Among these polytypes, the 4H-SiC structure with a bandgap of $3.2 eV possesses favourable electrical properties, including high electron mobility [3,4], making SiC an attractive candidate for "green energy" components in high-power electronic applications because of the potential for saving electric power and reducing CO 2 emission [5][6][7][8][9][10]. The mechanical behaviour of semiconductor materials is an important topic since the performance (such as functionality and reliability) of electronic devices strongly depends on their mechanical properties [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, such defects may also act as nanometer-scale sources of modified SPhP response that can be useful in the design of patterned nanophotonic or metamaterial devices. For instance, the incorporation of stacking faults in silicon carbide [69,70,[163][164][165][166][167][168][169][170][171][172][173] could provide a means to modify the Reststrahlen band and, therefore, the SPhP response of specific nanostructures or nanophotonic/metamaterial designs. Experimental evidence for this were reported by Ocelic et al [162] where it was demonstrated that the SPhP response could be severely damped via the patterned implantation of Be 3+ ions into a SiC surface using ion beam implantation.…”
Section: Lattice Properties and Optic Phonons: Dispersion Lifetimes mentioning
confidence: 99%
“…The SSF expansion in 4H-SiC is induced by the inversion of the SSF formation energy to the negative sign by electron trapping (and holes as excitons), in addition to the enhanced mobility of 30 partial dislocations (PDs) with Si core atoms in the glide-set core structure (30 Si(g) PDs), which form the leading edge of the SSF. [6][7][8][9][10][11][12] Such enhancement of PD motion is widely observed in semiconductors and is known as radiation-enhanced dislocation glide (REDG). 13 There are some reports on the REDG effect in 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%